ASSESSING WOMEN ULAMA’S PERSPECTIVES ON GENDER CONTESTATION AND LAW ESTABLISHMENT IN INDONESIA - Arifah Millati Agustina (Indonesian Journal of Law and Islamic Law (IJLIL), 2022)
In contrast with the history gender abroad, women's attitudes and relations with various sectors in Indonesia can be said to be completely different.  without distinguishing between both of them, local culture and approaches that affect one's perspective. This article describes the history of gender in Indonesia that is inseparable from the dogma and history of Indonesian women who fight for justice before the law, the variety of religions and cultures which are the main concerns that will distinguish the history of gender in Indonesia from others. This article narrates that gender as a perspective is strongly influenced by the doctrines of the ulama towards women through tafsir and methods. Women ulama brought up several gender issues in Indonesia which later became the product of a fatwa, including the elaboration of kyai Husein Muhammad highlighting how women's rights fighters in Indonesia seek to ratify the marriage law and bunyai Nur Rafiah’s argument saying that gender in Indonesia will never be separated from the method of Islamic studies which views the essential justice for which positions ultimate justice for women as the ultimate target, this argument leads to laws in Indonesia which are starting to lead to the mainstreaming of regulations. This discussion is further reinforced by kyai Faqihudin Abdul Kodir who argued that the goal of gender in Indonesia is the ratification of CEDAW, hence the issuance of UU no. 7 of 1984.